Clinical usefulness of metagenomic next-generation sequencing for the diagnosis of central nervous system infection in people living with HIV. (June 2021) - Chen, Jun; Zhang, Renfang; Liu, Li; Qi, Tangkai; Wang, Zhenyan; Song, Wei; Tang, Yang; Sun, Jianjun; Liu, Danping; Lin, Yixiao; Xu, Shuibao; Yang, Junyang; et al.
Highlights: Three-quarters (73.5%, 50/68) of central nervous system (CNS) infections were diagnosed by metagenomic next-generation sequencing (mNGS). Multiple CNS infections are common in people living with human immunodeficiency virus. The most common disease missed by mNGS tuberculous meningitis. Abstract: Objectives: To evaluate the clinical utility of metagenomic next-generation sequencing (mNGS) for the diagnosis of central nervous system (CNS) infection in people living with human immunodeficiency virus (PLWH) in a real-world situation. Methods: Cerebrospinal fluid (CSF) was sent for mNGS for PLWH who tested negative on all conventional tests but were still suspected to have CNS infection. A retrospective analysis was undertaken of the results and the clinical effect of mNGS on this cohort. The final diagnosis was adjudicated by a panel discussion following hospital discharge when the results of all tests and patients' responses to the empiric therapy were available. Results: Eighty-eight eligible PLWH, including 51 (58%) patients suspected of encephalitis and 34 (46.7%) patients suspected of meningitis, were included in the analysis. Sixty-eight (77.3%) patients were diagnosed with CNS infection, of which 50 were based on the pathogens identified by mNGS. The most common disease missed by mNGS was clinically suspected tuberculous meningitis, followed by clinically suspected non-tuberculous mycobacterial meningitis. The results from mNGS led to modification of treatment in 21 (23.9%) patients, and increased confidence in continuation of original therapy in 30 (34.1%) patients. During hospitalization, two (2.3%) patients died and 66 (75%) patients improved. Conclusions: mNGS of CSF is a useful tool for the diagnosis of CNS infection among PLWH. Further investigations are warranted to improve its sensitivity.